INVESTMENT ACTIVITIES OF INSUR- ANCE COMPANIES: PROBLEMS AND SO- LUTIONS - Muzafarovna, Babaeva Nargiza (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the investment potential of the insurance market, the mechanisms for the formation of funds by insurance companies, the terms and conditions of insurance companies’ reservation, the analysis of key financial and economic indicators of the insurance market, the approaches and views of foreign scholars on the insurance market. analysis of problems in the insurance market and stock markets, development prospects.